2014
DOI: 10.1248/bpb.b13-00459
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Reduces Cutaneous Tumor Necrosis Factor Alpha (TNF-α), IL-6 and IL-1β Levels and Ameliorates Skin Edema in Acute and Chronic Model of Cutaneous Inflammation in Mice

Abstract: Caffeic acid (3,4-dihydroxycinnamic acid, CA) has been reported to have anti-inflammatory activity in animal models. However, the mechanisms underlying the anti-inflammatory effects of CA in skin inflammation are only partially understood. The present study was designed to investigate the effects and mechanisms of CA on acute and chronic skin inflammation in mice and the effect of CA in keratinocytes in vitro. The results showed that topical treatment with CA inhibited 12-O-tetradecanoyl-phorbol-13-acetate (TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 23 publications
3
50
2
1
Order By: Relevance
“…3). The effective dosages of CA in TPA-induced chronic inflammation model were 2, 4, and 6 % [28] whereas our results showed that CAPE was effective at 0.5 and 1 % in hapteninduced chronic dermatitis model (Fig. 5).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…3). The effective dosages of CA in TPA-induced chronic inflammation model were 2, 4, and 6 % [28] whereas our results showed that CAPE was effective at 0.5 and 1 % in hapteninduced chronic dermatitis model (Fig. 5).…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, CAPE was effective in vivo at the concentrations as low as 0.5 %. Recent report showed that the application of 6 % CA suppressed multiple TPA challenge-induced ear edema only by *24 % [28] while in our study, CAPE almost completely blocked TPA-induced ear edema at 0.5 % (Fig. 3).…”
Section: Discussioncontrasting
confidence: 43%
“…Interestingly, Caffeic acid and Ferulic acid, the representative active ingredients in LJ (She and Zhu, 2008), exhibit low DL values, although their OB values meet the standards. They show potent antisepsis and anti-inflammatory effects (Ma et al, 2010;Zhang et al, 2014;Tang et al, 2014) and could be selected for further evaluation. Based on all these considerations, it was reasonable to believe that five could be listed as potential active ingredients.…”
Section: Csmentioning
confidence: 99%
“…CA is also a potent 5-LOX inhibitor [9], as well as a potent antioxidant [10]. In the inflammatory process, CA has been demonstrated to downregulate NF-κB and inhibits tumor necrosis factor alpha (TNF-α), IL-6, IL-1β [11]. CA phenethyl ester, a derivative of CA, has been reported to protect IR-induced renal injury [12].…”
Section: Introductionmentioning
confidence: 99%